2020
DOI: 10.1029/2019jd032024
|View full text |Cite
|
Sign up to set email alerts
|

Time Evolution of Satellite‐Based Optical Properties in Lightning Flashes, and its Impact on GLM Flash Detection

Abstract: The GOES‐16 Geostationary Lightning Mapper (GLM) detection efficiency (DE) is studied over a full year (2018/19) in central Florida using the Kennedy Space Center Lightning Mapping Array (KSC LMA). Mean daily flash DE was 73.8%, and detection was highest during nighttime hours. GLM reported 86.5% of the LMA flashes that had coincident cloud‐to‐ground return strokes reported by the U.S. National Lightning Detection Network. Results also reveal that flash size and duration are critical parameters influencing GLM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
82
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(103 citation statements)
references
References 30 publications
12
82
1
Order By: Relevance
“…Here we used the local pixel footprint area ( a ) which in the corner of the field of view of the instruments on the ISS is significantly larger than in nadir direction. For a detailed explanation about the conversion, refer to Zhang and Cummins (2020, Appendix A). For conversion of the photometer flux density values (W m −2 ), we multiplied by sample time, yielding q /(π D 2 /4), then used their formula A.7 (left side) where it can be noted that pixel footprint area a divided by pixel solid angle ω yields distance squared ( z 2 ), eliminating the need to know the emitting area.…”
Section: Methods and Datamentioning
confidence: 99%
“…Here we used the local pixel footprint area ( a ) which in the corner of the field of view of the instruments on the ISS is significantly larger than in nadir direction. For a detailed explanation about the conversion, refer to Zhang and Cummins (2020, Appendix A). For conversion of the photometer flux density values (W m −2 ), we multiplied by sample time, yielding q /(π D 2 /4), then used their formula A.7 (left side) where it can be noted that pixel footprint area a divided by pixel solid angle ω yields distance squared ( z 2 ), eliminating the need to know the emitting area.…”
Section: Methods and Datamentioning
confidence: 99%
“…Analyses of optical and combined optical/RF emissions from lightning have provided a wealth of insights on processes involved in the lightning discharge (Bitzer, 2017; Noble et al, 2004; Østgaard et al, 2013; Peterson et al, 2017; Peterson & Rudlosky, 2019; Suszcynsky et al, 2000; Thomas et al, 2000; Ushio et al, 2002; Zhang & Cummins, 2020). Hence, the capability of ISS LIS to detect the optical fingerprint of lightning on a global scale with a relatively high DE makes for a unique data set to compare with optical, RF, and other measurements of lightning and related atmospheric electrical phenomena.…”
Section: Current and Future Cross‐platform Sciencementioning
confidence: 99%
“…Just a single flash observation provides confirmation of a convective system to the AWC, enabling aircraft to be rerouted safely around these systems. Due to reduced DE during the day, as well as coarser pixel resolution off boresight, weaker and smaller size flashes are not as well detected by the GLM instruments (Zhang & Cummins, 2020). For these reasons AWC and other NWS service centers have found that ISS LIS augments their confidence in GLM (and ground‐based) detection of lightning especially over oceanic regions (Goodman, Blakeslee, Pettegrew, Terborg, Stevenson, et al, 2020).…”
Section: Analysis and Findingsmentioning
confidence: 99%
“…It is worth noting that the number of return strokes per flash was not the only factor that explains the flash duration. Changes in the electric field and current intensity will also affect the flash duration [86,124]. Figure 8 shows a comparison of the statistical results for the characteristic parameters of radiation in the LMI and LIS flashes.…”
Section: Optical Radiation Characteristics Of Lightning Signalsmentioning
confidence: 99%